Analisis Video Animasi Inovatif dalam Pembelajaran IPA pada Masa Pandemi Covid-19 di MIM Girimargo Miri Sragen Tahun Pelajaran 2020/2021 - Hera Heru Sri Suryanti; Anggit Grahito Wicaksono; Augustina Dewayanti (FKIP, PGSD, Universitas Slamet Riyadi, 2021)
The study's aims are as follows: 1) describe the scientific learning process using creative animated films; and 2) analyze the benefits and drawbacks of innovative animated movies in science learning during the Covid-19 epidemic. The research method employed is descriptive qualitative research. The study's findings: 1) determine the response of students by providing science material with innovative animated video media; 2) the use of animated video media in online learning makes it easier for students to understand science material delivered by subject teachers; and 3) the benefits of animated videos, which can ease the teacher's task and serve as a tool to help the teacher when giving science material. Make it easy for pupils to grasp the subject, inspire students to be excited about studying, and encourage students to study science topics. The downsides of animated videos are that the process of creating them takes a long time, and there is a requirement for animation software.